Ahead of the curve? : UN ideas and global challenges - Emmerij, Louis; Jolly, Richard; Weiss, Thomas G. (Thomas George), 1946- (United Nations intellectual history project., 2001)
Ideas and concepts are arguably the most important legacy of the United Nations. Ahead of the Curve? analyzes the evolution of key ideas and concepts about international economic and social development born or nurtured, refined or applied under UN auspices since 1945. The authors evaluate the policy ideas coming from UN organizations and scholars in relation to such critical issues as decolonization, sustainable development, structural adjustment, basic needs, human rights, women, world employment, the transition of the Eastern bloc, the role of nongovernmental organizations, and global gove.